(untitled) (Research, Society and Development, 2022)
Introduction: Health education is a health promotion activity, as in addition to involving programs related to a certain aspect of health, it also promotes well-being and necessary changes in lifestyle. Objective: To analyze aspects of the lifestyle and well-being of education workers, through the Pentacle of Well-being, in a health education approach. Methodology: This is an exploratory, descriptive research, with a quantitative approach, carried out with 30 education workers from the 6th Regional Education Coordination of Rio Grande do Sul, which used the application of the well-being pentacle. Discussion: The well-being pentagram has five fundamental aspects of the lifestyle that are evaluated, they are nutritional characteristics, the level of habitual physical activity, preventive behavior, stress control and quality in relationships. Final considerations: The data found allowed the understanding and crossings that lead the lives of public servants, as well as the strengths and weaknesses regarding the aspects that promote the quality of life and well-being of these participants.